THE ROLE OF HUMAN CAPITAL ON REMOTE AUDIT THROUGH A QUALITY AUDIT APPROACH - Andriani Kusumaningrum; Harsanto Harsanto; Kumaratih Sandradewi; Afu Ichsan Pradana (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2022)
The condition of the prolonged Covid-19 pandemic entering its third year, requiring the fulfillment of health protocols and social distancing policies, including the work from home policy, is very influential in the implementation of audits, which should be the largest portion in field activities. Management and supervision as a function of controlling the rotation of the business wheel, is a link in terms of the responsibility for governance of business management to prepare and present financial statements and other relevant disclosures based on the best judgment and analysis of the latest facts and events after the reporting date that can predictable. Reliable human resources in driving the pace of change and change from various sides as part of the company's adaptive response to the prolonged Covid-19 pandemic conditions in the supervision department and audit system in business organizations are very key in maintaining audit quality and obtaining audit evidence. sufficient and appropriate to support the audit opinion through procedures for gathering audit evidence, revising the process for identifying and assessing the risks of material misstatement, and changing planned audit procedures or performing alternative or follow-up audit procedures as appropriate. The role of reliable human resources is part of the company's wealth ( human capital ) in collaborating with information technology and investing in technology as a solution to facilitate communication between the auditor department and business management using remote audit potential or known as remote audit while maintaining audit quality and optimizing the supervision and control of the business wheel. The implementation of remote auditing requires auditors to improve the ability to use technology, it is necessary to have human resource competencies that can always be improved through adequate training and education, so that increasing competencies will improve audit quality, in line with increasingly qualified human capital will affect the process. audit and is directly proportional to improving audit quality. Keywords: Covid-19 pandemic, remote audit , human capital , information technology